BEBERAPA SIFAT IDEAL GELANGGANG POLINOM MIRING: SUATU KAJIAN PUSTAKA - AMIR KAMAL AMIR (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2010)
Let R be a ring with identity 1 and s be an endomorphism of R and d be a left s - derivation . Theskew polynomial ring over R in an indeterminate x is: R[x;s ,d ] = f (x) = anxn +L+ a0 | ai Î Rwith xa =s (a)x +d (a) The aim of this research is to investigate the ideals in the above skewpolynomial ring in case of d = 0 . Precisely, we will investigate the following: (1) the ideal of skewpolynomial ring D[x;s ] ; (2) the ideal prim of skew polynomial ring K[x;s ] ; and (3) the s - primideal of skew polynomial ring D[x;s ] .